Analisis Statistika Keandalan Struktural Dalam Teknik Sipil - Zebua, Dermawan; Mendrofa, Putra Sudi Selamat; Telaumbanua, Frans Tiven; Mendrofa, Rifki Wahyudi; Laoli, Putra Jaya (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2024)
Structural reliability statistical analysis is an essential approach in civil engineering to assess a structure's ability to maintain its function and safety during its service life, despite uncertainties in materials, loads, and environmental conditions. This study aims to explore the application of statistical methods in reliability evaluation, which includes probabilistic analysis of uncertain parameters and failure probability calculations. This approach involves the use of probability distribution theory, Monte Carlo simulations, and other numerical methods to estimate the reliability level of a structure. The results of the analysis provide insights into how variability in materials and loads can affect the stability of structures, and offer a basis for decision-making in the design and maintenance of civil structures. Thus, this reliability analysis helps engineers design safer, more efficient, and sustainable structures while minimizing the risk of failure that could impact public safety and cause economic losses.